The Effects of Algal Blooms on Oxygen Levels in Lakes Babati and Eyasi, Tanzania - Buriyo, Amelia S.; Mganga, Nyatwere D.; Melchiory, Mary (Tanzania Journal of Science, 2024)
Globally aquatic ecosystems are reportedly overwhelmed by algal blooms due to excessive deposition of nutrients which ultimately cause hypoxia, leading to massive fish death. This study aimed at assessing the relationship between algae contents and dissolved oxygen (DO) in Lake Babati which is threatened by anthropogenic activities, whereas Lake Eyasi was used as a control. Algae contents (chlorophyll a), DO and surface water temperature were measured using standard methods. Results revealed that the mean algae content was significantly higher (4.47±0.88 mg/L) in Lake Babati than in Lake Eyasi (1.6±0.45 mg/L) (P < 0.05) and was beyond the standard permissible levels for domestic water supply and healthy ecosystem. Conversely, DO was significantly lower in Lake Babati than in Lake Eyasi (P < 0.05). There was no significant difference in water temperature in the two lakes (P > 0.05). Furthermore, there was an inverse relationship between algae content and DO in Lakes Eyasi and Babati (r = -0.88 and r = -0.30, respectively) suggesting that algal bloom is partly responsible for lowering DO. Responsible authorities are advised to enforce management policies and regulations to control unsustainable activities around these lakes that contribute to nutrient loading resulting into overgrowth of algae.